Problems on chromatic polynomials of hypergraphs - Ruixue Zhang; Fengming Dong (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2020)
Chromatic polynomials of graphs have been studied extensively for around one century. The concept of chromatic polynomial of a hypergraph is a natural extension of chromatic polynomial of a graph. It also has been studied for more than 30 years. This short article will focus on introducing some important open prblems on chromatic polynomials of hypergraphs.